Effects of spermine on ileal physical barrier, antioxidant capacity, metabolic profile and large intestinal bacteria in piglets. Issue 45 (17th July 2020) - Liu, Guangmang; Mo, Weiwei; Cao, Wei; Wu, Xianjian; Jia, Gang; Zhao, Hua; Chen, Xiaoling; Wu, Caimei; Wang, Jing
Abstract : Spermine, a polyamine, exerts important roles in alleviating oxidative damage, improving immunity, increasing antioxidant status and digestive enzyme activities, and promoting the development of small intestine. Abstract : Spermine, a polyamine, exerts important roles in alleviating oxidative damage, improving immunity, increasing antioxidant status and digestive enzyme activities, and promoting the development of small intestine. However, information is not available regarding the effects of spermine supplementation on gut barrier function, intestinal microbiota and metabolic profile in piglets. Therefore, this study was designed to explore the effect of spermine administration on these parameters. The experiment was conducted on twenty 12 day-old suckling piglets, which were allocated either to the group fed basal formula milk (control group) or to that fed a basal formula milk that contained spermine (0.4 mmol kg −1 BW per day) for 3 days. Caecal and colonic digesta and ileal tissues were collected at the end of the three-day feeding experiment. The results were as follows: (1) supplementation with spermine increased glutathione S -transferase (GST) capacity by 27.84% and glutathione content by 18.68% in the ileum ( P < 0.05). (2) Glutathione peroxidase 1 (GPx1), catalase (CAT), GST, nuclear factor erythroid 2-related factor 2 (Nrf2) and Kelch-like ECH-associated protein1 (Keap1) mRNA levels in ileum were increased in the spermine-supplemented group in contrast to those in the control group ( P < 0.05). (3) The spermine-supplemented group increased zonula occludens-1 (ZO-1) (by 42.0%), ZO-2 (by 101.0%), occludin (by 84.0%), claudin 2 (by 98.0%), claudin 3 (by 121.0%), claudin 12 (by 47.0%), claudin 14 (by 68.0%) and claudin 16 (by 73.0%) mRNA levels in ileum relative to the control group ( P < 0.05). (4) Supplementation with spermine increased ZO-2 and occludin mRNA levels in ileum by reducing myosin light chain kinase (MLCK) (by 23.0%) mRNA level. (5) Spermine supplementation increased choline, glycerolphosphocholine, creatine and serine levels, and decrease alanine, glutamate, lysine, phenylalanine, threonine, lactate, tyrosine levels in ileum ( P < 0.05). (6) The population of Lactobacilli, Bifidobacteria and total bacteria increased, but the number of Escherichia coli decreased in the caecal and colonic digesta after spermine supplementation ( P < 0.05). In summary, dietary spermine supplementation promotes ileal health by enhancing antioxidant properties, improving ileal barrier function, modulating metabolic profiles, and maintaining large intestinal microbial homeostasis.